Relasi Murshid dan Murid dalam Bimbingan Tarekat Shādhilīyah di Pesulukan Thoriqot Agung Tulungagung - Chabib Musthofa (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
This article attempts to reveal the relation of murshid and murīd (pupil) of the Tarekat Shādhilīyah at Pesulukan Thoriqot Agung (PETA) in Tulungagung East Java. The author discusses the pattern of constructive relation between murshid and his pupils to build an objective social reality of the tariqa in terms of its teaching and ritual aspects. This moment subsequently becomes a medium of adaptation of the pupils. It helps the pupils reach spiritual happiness and internalize it into his/her consciousness and behaviors. Within such relation, social construction affirms that community is a result of human’s production, and it stands beyond the zone of an external phenomenon. This external phenomenon consists of material and non-material subjects. In time, the external phenomenon becomes an objective reality, which forms other people’s understanding and behavior in other different periods. Murshid has been the main subject within a tariqa who is capable of coloring the spiritual realm of his pupils. The plot of murabbī al-rūḥ (spiritual educator) attached upon murshid is not a mysteriously hidden, abstract, and unseen epithet. Instead, this spiritual status is applied in his social action and behavior, and it colors the spiritual actions of his murīd.